Migrantki jako grupa szczególnie narażona na naruszenie ich praw : analiza wybranych instrumentów ochrony w prawie azylowym i migracyjnym - Kosińska, Anna Magdalena (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The aim of this paper is to present the most important legal instruments regulating the migrant women’s situation seeking asylum or returning to the country of origin (in the EU law system and the European courts’ judgments). Nowadays women are becoming more and more important actors in European and global migratory movements. The problem of protection of their rights is extremely important in the situation of so called irregular migration or during the asylum procedures. Women should be treated under the EU law provisions concerning migration policies as a vulnerable group. Their rights should be carefully protected in the event of the ill treatment and the high risk of the potential violations. The confirmation of the importance of the analyzed issue are numerous judgments of the European Court of Human Rights as well as the NGOs activity
Keywords: migrant women; migration; refugees; migration law; CEAS